Art and industrial exhibits and national exhibits as forerunners of the colombian national artists’ salon (2006)
The first Colombian Artists’ Salon (1931) is commonlyconsidered as the only antecedent to the official NationalArtists’ Salon founded in 1940. Nevertheless, annualnational exhibitions where held between 1904 and 1931,that should be considered as forerunners. The inquiryinto the general conditions that embodied those exhibits,in contrast with the institutional definition of an artsalon (provided by the 18th century French Academy),allows the author to provide new antecedents for theNational Salon and a better understanding of Colombianart during the first decades of the 20th century.